Keefektifan Achievement Motivation Training untuk Meningkatkan Motivasi Berprestasi Siswa Sekolah Menengah Pertama - Putra, Edwindhana Mareza; Handarini, Dany M. (citeus, 2024)
The particular study aimed to determine the effectiveness of achievement motivation training (AMT) in increasing the achievement motivation of junior high school students. The study used an interrupted time-series design which conducted on an intact group consisting of eight subjects. Data measurements carried out three times in the pre-test and post-test conditions with six forms of achievement motivation scale. The AMT intervention in the psychoeducation frame consists of two strategies, namely achievement thinking and action strategies which are carried out in 12 sessions. The results showed that there is a difference between achievement motivation scores before and after AMT interventions.